2012
DOI: 10.1242/dev.077743
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal activation of let-7-C microRNAs via EcR is required for adult Drosophila melanogaster morphology and function

Abstract: Steroid hormones and their nuclear receptors drive developmental transitions in diverse organisms, including mammals. In this study, we show that the Drosophila steroid hormone 20-hydroxyecdysone (20E) and its nuclear receptor directly activate transcription of the evolutionarily conserved let-7-complex (let-7-C) locus, which encodes the co-transcribed microRNAs miR-100, let-7 and miR-125. These small RNAs post-transcriptionally regulate the expression of target genes, and are required for the remodeling of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 41 publications
6
91
1
Order By: Relevance
“…Previous studies showed that miR-100 expression was delayed and its expression level was reduced during development compared to let-7 and miR-125 (ref. 37). In this study, we found that the expression of pri-let-7-C did not exhibit cycling.…”
Section: =2498±004 H Pdf-gal4/+;uas-let-7/+mentioning
confidence: 46%
See 4 more Smart Citations
“…Previous studies showed that miR-100 expression was delayed and its expression level was reduced during development compared to let-7 and miR-125 (ref. 37). In this study, we found that the expression of pri-let-7-C did not exhibit cycling.…”
Section: =2498±004 H Pdf-gal4/+;uas-let-7/+mentioning
confidence: 46%
“…The presence of a GFP signal in clock neurons in let-7-C-GAL4:UAS-EGFP flies further supports the action of let-7 in the central pacemaker. To further investigate the expression of let-7 and its target Cwo in the brain, we also analysed two transcriptional reporters that contain almost the entire first intron of let-7-C (let-7-Cp12.5kb::lacZ) or just the 20-OH ecdysteroid (20E)-responsive 3.3 kb fragment (let-7-Cp3.3kb::lacZ) with cwo-Gal4 driving GFP 37 . The Cwo reporter was prominently expressed in the LNvs, the PI neurons and the SG (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations